The Abundance of Gonyaulax polygramma and Chaetoceros sp. Causing Blooming in Ambon Bay, Maluku - Irma Kesaulya; Delta R. Rumohoira; A. Saravanakumar (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2022)
This study examines the first occurrence of non-toxic dinoflagellate blooming of Gonyaulax polygramma and Chaetoceros sp in Ambon Bay that occurred for almost three weeks in January 2019 and it caused the watercolor became red brown. The objective of this study was to identified phytoplankton species and their abundance that cause red tide in the Inner Ambon bay.  Phytoplankton samples were collected, temperature, salinity and Secchi depth were measured simultaneously on the 11th and 21st January 2019 (nortwest monsoon) at fifteen sampling stations in Inner Ambon Bay. The results show that the maximum abundance of Gonyaulax polygramma, Chaetoceros affinis, C. danicus and C. decipiens were found in the greatest concentration up to 20×109, 9.0x106, 5.8x106 and 3.8x105 cells.L-1, respectively. They were found either in the form of a single cell or in chains. The very high abundance of cells of those species made the waters become red brown but there was no reports of fish killed during this red tide phenomena. This is the first time report of blooming phytoplankton Gonyaulax polygramma, Chaetoceros affinis, C. danicus and C. decipiens occurred in Ambon bay during the dry season where the recorded waters temperature and salinity ranged from 30-32ºC and 29-33 psu, respectively and the secchi depths ranged from 2 to 6m.